Miscegenation and Hybridism in Heliodorus’ Aethiopica - Graebin, Geruza de Souza (Revista Archai, 2020)
Amongst all the works within the genre, the novel Aethiopica stands out for its composition techniques. In fact, the author Heliodorus shows the ability of both innovate and astonish readers, by creating scenes and characters, as well as distinguished and completely original situations. Taking the verb Î¼Î¹Î±Î¯Î½Ï‰ as a red string, since it is recurrently used in Heliodorus’ work and also summarizes the idea of miscegenation, some pieces of the romance in which the idea of hybridity, opposition of contraries or, still, the overlapping of elements are highlighted and used in the present study. The results show that miscegenation, besides being a sign of Helidorus’ style, is a technique that gives rise to questioning about social, geographical and cultural conventions of that time.